Quality of Services Provided by Social Care Centres for the Elderly in Latvia: Challenges and Possible Solutions - Stals, Edgars; Tsaurkubule, Zhanna; Konstante, Rita (Jakość usług świadczonych przez ośrodki pomocy społecznej dla osób starszych w Łotwie: wyzwania i możliwe rozwiązania, 2023)
Latvia faces the challenges of an ageing society, which increases the demand for long-term social care services at municipal level. The aim of the work was to address the problematic issue related to the quality assurance and control of the care service for people of retirement age and the improvement of this quality control process in SCCs in Latvian municipalities. In addition, an analysis of the administrative data of social care homes in Latvia was carried out. The authors have concluded that currently, the arrival at an objective assessment of SCC service quality is impossible. The content of this work allows to argue that quality indicators (QI) should be integrated within SCC quality assessment, thus providing several advantages in terms of service planning and quality assessment, and the use of data for high quantity research.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 2, s. 134-144
Keywords: Latvia; service quality; social care centres; quality indicators; jakość usług; wskaźniki jakości; Łotwa; ośrodki pomocy społecznej